Luaran Penelitian Non-Tradisional dalam Linguistik di Era Digital: Studi Kasus VerbInd Pangkalan Data Verba Bahasa Indonesia Berbasis Korpus - Rajeg, Gede Primahadi Wijaya (Udayana University, 2026)
The 21st-century research ecosystem highlights the importance of non-traditional outputs such as datasets and software, alongside articles and books. In the Humanities, digital technologies enable data to be presented more openly through online databases. This paper introduces VerbInd, an open-access online database of morphologically complex verbs in Indonesian, built from corpus texts and processed through computational morphological parsing with further manual verification and editing. The paper demonstrates the use of VerbInd in quantitative research on Indonesian verbal morphology and morphosyntax (particularly voice alternation), resulting in traditional outputs, namely book chapters. It also briefly compares VerbInd with the sixth edition of the online Kamus Besar Bahasa Indonesia (KBBI), emphasizing their potential complementarity as linguistic research resources.